PENYAKIT ZOONOSIS DENGAN PERHATIAN KHUSUS PADA SCHISTOSOMIASIS JAPONICUM : SEBUAH TINJAUAN - Raflizar Raflizar; Mohammad Sudomo (Berita Kedokteran Masyarakat (BKM), 2019)
Zoonotic disease with special attention to Schistosomiasis japonicum: an overview Schistosomiasis is a zoonotic parasitic disease with a very complex transmission cycle. Its transmission concerns freshwater snails and 40 species of mammals that act as reservoir hosts. Research and treatment of schistosomiasis in animals, both domestic and wild animals is still very little. There are three species of Schistosoma which are zoonotic diseases of S. mansoni, S japonicum and S mekongi. Schistosoma is found in China, Japan, the Philippines, Indonesia, Africa, the Middle East, South America, the Caribbean islands and countries along the Mekong River. In China the contribution of humans to the transmission of schistosomiasis has been greatly reduced after several decades of elimination of schistosomiasis. In Indonesia, schistosomiasis is only found in the Lindu plateau in Sigi, Napu and Bada districts in Poso District, Central Sulawesi. Schistosoma infects mammals, namely: cattle, buffalo, horses, dogs, pigs, ferrets, deer and various types of mice. Schistosomiasis eradication program in Central Sulawesi involving all sectors including the livestock sector. As long as there is an intermediate animal reservoir and snail, reinfection will occur continuously. Because of its complex zoonotic schistososmiasis transmission becomes a major barrier problem for the elimination of schistosomiasis. Community empowerment is very important, because without public awareness of parasitic diseases that threaten them, the parasitic disease eradication program will not work well.